Ruby Lampard interviewed by Loretta Thomson in the Australia 1938 oral history project - Lampard, Ruby, 1899-; Thomson, Loretta; Australia 1788-1988: A Bicentennial History; Australia 1938 Oral History Project (1988)
Lampard speaks of her family background; the Depression; marriage in 1923; raising her children; family lifestyle; her husband's farm work; living conditions; family farm; recreation.
Transcript unavailable.
Cassette 2 is blank.
Recorded by the Australia 1938 Oral History Project as research for the book Australians 1938 from the series Australians, a historical library.
Digital master available
Timed summary available.
Keywords: Lampard, Ruby, -- 1899- -- Interviews; Rural conditions; Victoria -- Social conditions -- 1901-1945.